Exploring the Knowledge of Tutors on Gender Equity and Equality in Teacher Education in Uganda - Lubega , Kansiime Margaret (African Journal of Education,Science and Technology (AJEST), 2014)
This study investigated on Gender Equality and Equity in Teacher Education in Uganda. The aim of the study was to examine the extent to which pre-service teacher education prepares future teachers to be gender responsive in their teaching career. A total sample of 90 tutors was obtained from 15 government teacher training colleges. Questionnaires, interviews to key stake holders in teacher education in the Ministry of Education and observations were used for data collection. Data was analyzed by using simple random sampling. The study revealed that though tutors understood what the term gender meant their socialization process continues to perpetuate gender inequality in their way of life. This socialization process impacts on how teacher trainers treat male and female students. The study found that tutors associated female students with weak issues while male students where associated with the hard work and good performance in class. The study concludes that low levels of gender responsiveness reinforces the superiority of males over females. The research demonstrated that the tutors‟ gender played a significant role in influencing how male and female students learn and conceptualize what they are taught. The outcome was the continuous gender inequalities and inequities in our societies. The study made recommendations that would help teachers to unlearn, relearn and reconstruct the way they perceive gender issues and how they teach and train teachers to- be who are the foundation of education systems worldwide.